2017
DOI: 10.1021/acs.iecr.7b03468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Size on the Structural Transition and Magnetic Properties of Nano-CuFe2O4

Abstract: Advances in the field of chemistry often involve nanoparticles, in which the structural transition is surprisingly different from the bulk material, and the difference between them is mainly attributed to the size of the nanoparticles. In this paper, tetragonal nano-CuFe 2 O 4 (t-CuFe 2 O 4 ) with different sizes ranging from 32 to 79 nm was prepared using the high temperature solid phase method. The structural transition of nano-CuFe 2 O 4 from tetragonal to cubic was determined by differential scanning calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Furthermore, the qualitative change regularity of the temperature of structural transition with particle size agrees with previous reports. 19,20,35 Because of the larger surface energy of nanocrystals with smaller sizes participating in the phase transition process, the energy needed for this transition is reduced, allowing the phase transition to occur at a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the qualitative change regularity of the temperature of structural transition with particle size agrees with previous reports. 19,20,35 Because of the larger surface energy of nanocrystals with smaller sizes participating in the phase transition process, the energy needed for this transition is reduced, allowing the phase transition to occur at a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Our results on the influence regularity of particle size on the enthalpy of structural transition coincide with the above theoretical analysis of eq 13 and previous reports. 19,20,36 To explore the effect of particle size on the entropy of structural transition of nano-γ-Fe 2 O 3 , the relationship between the transition entropy of nano-γ-Fe 2 O 3 and the inverse particle size was evaluated, as shown in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cui et al [43] demonstrated that the crystallinity densities of the two transitions are equal. Zhang et al [44] successfully determined the Néel phase transition temperature of Fe 2 O 3 when considered system transitioned from the maghemite phase to the α hematite phase, namely T Ntot = 623 K at D = 4 nm and T Ntot = 723 K at D = 24 nm. Mendili et al [45], Wenger et al [46] have successfully determined that the magnetization (M) of γ-Fe 2 O 3 nanoparticles increases when D increases (from D = 2 nm to D = 4 nm).…”
Section: Introductionmentioning
confidence: 99%